Liberia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2000)
This paper provides an overview of economic developments during 1997-99 in Liberia. A large part of the deterioration in the debt-stock ratios over the past decade reflects the accumulation of arrears. This is shown clearly in the increase in the debt per capita ratio. Provisional GDP estimates by source have been prepared by IMF staff in collaboration with the Liberian government. These estimates suggest a very sizable decline during the war and a strong initial post-war recovery based on crop production and export data.